Epidemiology of Entamoeba histolytica , Giardia lamblia and Blastocystis hominis in Basra Province - Haydar Abdul- Jaleel Rhadi [ H A Rhadi] (Institute of Medico-legal Publications Pvt Ltd, 2021)
To evaluate the intestinal parasites in (auditors) reviewers in Basra province. The present study recorded (188) persons infected with Entamoeba histolytica infection ( 21.19%) , Giardia lamblia (61) cases (6.8%), The highest infection with Entamoebahistolyticain May (27) cases ,Giardia lamblia in December (10) cases ,The lowest infection with Entamoeba histolytica in February.( 7) cases, Giardia lamblia (2) cases in August .the number infected with the parasite Entamoeba histolytica ( 100) male and 88 , 30male and 31 female infected with Giardia lamblia ;17 and 19 of male and female. The highest infection with Entamoeba histolytica in male (14) cases in May ,6 male infected with GiardiaThe lowest infection with Entamoeba histolyticain male (3) cases in February, The highest infection with Entamoeba histolytica in female (13) cases in May , 4 cases infected with Giardia lamblia in both September, November and December The highest infection with Entamoeba histolytica (52) cases at age ( 21-30) years, with Giardia lamblia ( 14) cases at age ( 11- 20) years, with Blastocystis hominis (7) cases at both age ( 1-5) years and (21-30) years. The lowest infection with Entamoeba histolytica (12) cases at age ( 1-5) years , Giardia lamblia ( 5 ) cases at age ( 1-5) years , Blastocystis hominis (5 ) cases at both age (6- 10) years and (41- 60 over) years.The study was conducted in Basra region between2nd January and31st December2019 .